Cannabis and the health and performance of the elite athlete - Ware, M. A.; Jensen, D.; Barrette, A.; Vernec, A.; Derman, W. (Clinical Journal of Sport Medicine, 2018)
Objective: Cannabis (marijuana) is undergoing extensive regulatory review in many global jurisdictions for medical and nonmedical access. Cannabis has potential impact on the health of athletes as well as on performance in both training and in competition. The aim of this general review is to identify and highlight the challenges in interpreting information with respect to elite athletic performance, and to point to important research areas that need to be addressed.